ARE WE PREPARED FOR INFLUENZA PANDEMIC? - Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2005)
The United Nations has been warning about a bird flu pandemic for about one year now. These warnings were merely '˜suggestions' a few months back, but recently with the mutation reports of the virus these warnings have also '˜mutated' to '˜alarms'. These alarms have led to panic stockpiling of antiviral drugs by affluent countries, United Nations and black marketers. The World Health Organization (WHO) has reported an outbreak of Avian Influenza in birds in several countries in Asia.1,2 Avian influenza is a contagious viral infection with a potential to affect all species of birds, and rare transfer to humans. Avian influenza virus has 15 known types that infect wild bird populations (mainly water birds). In wild birds this infection is without symptoms, therefore the infected birds carry on with their normal life. The bird feces and contaminated water or dust spreads avian influenza to domestic ducks and to the other poultry. In domestic birds the disease is severe. This very contagious virus then spreads rapidly in poultry flocks killing whole population of domestic birds in some areas.